Intelligence, educational attainment, and brain structure in those at familial high-risk for schizophrenia or bipolar disorder - de Zwarte, Sonja M C; Brouwer, Rachel M; Agartz, Ingrid; Alda, Martin; Alonso-Lana, Silvia; Bearden, Carrie E; Bertolino, Alessandro; Bonvino, Aurora; Bramon, Elvira; Buimer, Elizabeth E L; Cahn, Wiepke; Canales-Rodríguez, Erick J; et al. (Human brain mapping, 2022)
First-degree relatives of patients diagnosed with schizophrenia (SZ-FDRs) show similar patterns of brain abnormalities and cognitive alterations to patients, albeit with smaller effect sizes. First-degree relatives of patients diagnosed with bipolar disorder (BD-FDRs) show divergent patterns; on average, intracranial volume is larger compared to controls, and findings on cognitive alterations in BD-FDRs are inconsistent. Here, we performed a meta-analysis of global and regional brain measures (cortical and subcortical), current IQ, and educational attainment in 5,795 individuals (1,103 SZ-FDRs, 867 BD-FDRs, 2,190 controls, 942 schizophrenia patients, 693 bipolar patients) from 36 schizophrenia and/or bipolar disorder family cohorts, with standardized methods. Compared to controls, SZ-FDRs showed a pattern of widespread thinner cortex, while BD-FDRs had widespread larger cortical surface area. IQ was lower in SZ-FDRs (d = -0.42, p = 3 × 10-5 ), with weak evidence of IQ reductions among BD-FDRs (d = -0.23, p = .045). Both relative groups had similar educational attainment compared to controls. When adjusting for IQ or educational attainment, the group-effects on brain measures changed, albeit modestly. Changes were in the expected direction, with less pronounced brain abnormalities in SZ-FDRs and more pronounced effects in BD-FDRs. To conclude, SZ-FDRs and BD-FDRs show a differential pattern of structural brain abnormalities. In contrast, both had lower IQ scores and similar school achievements compared to controls. Given that brain differences between SZ-FDRs and BD-FDRs remain after adjusting for IQ or educational attainment, we suggest that differential brain developmental processes underlying predisposition for schizophrenia or bipolar disorder are likely independent of general cognitive impairment.
Keywords: inteligence; Genetic Predisposition to Disease; neuroimaging; Cognitive Dysfunction; Family; Neuroimaging; Schizophrenia; bipolární porucha; Intelligence; education; stupeň vzdělání; Bipolar Disorder; magnetická rezonanční tomografie; Magnetic Resonance Imaging; Humans; neurozobrazování; bipolar disorder; schizophrenia; kognitivní dysfunkce; relatives; schizofrenie; rodina; genetická predispozice k nemoci; Educational Status; intelligence; lidé